Characteriza of activated carbon from rambutan seed (nephelium lappaceum) as natural precursor - Siti Fatimah Zahra Mohd Sarif (School of Environmental Engineering University Malaysia Perlis, 2011)
Activated carbons were prepared from rambutan seed with impregnation of zine chloride as activating agent. In order to find its characteristics, different zinc chloride to rambutan seed ratio (0.5 and 2) and activation temperature (450 cand 650 c) was employed. The carbonization occured in a tube furnace with flow of nitrogen gas at rate of 0.5 L/min. The results showed that at higher impregnationratio and carbonization temperature produced a wider BET surface area of activated carbon that was 9.8761m²/g with ratio 2 and temperature of 650 c . Total pore volume also increased with increased of these two factors with highest value of16.52E-03cm³/g. However activation yield was increased with decreasing of carbonization temperature and increasing in impregnation ratio.